Reviving Springs: An eight step methodology - Mukherji, Aditi (2017)
Springs, also called dhara, mool, kuwa, naula, and chasma, are, the most important source of water for millions of people in the midhills of the Hindu Kush Himalayas. Spring water is used for drinking, irrigation, domestic, and religious purposes. They also perform important ecological functions, like supporting local vegetation and wildlife and maintaininng baseflow in rivers. The methodology integrates aspects of physical and social sciences, and is just as useful for researchers as it is for field practitioners. The step-wise approach is relatively easy to follow and each step generates scientific information while also allowing project implementers to invest in infrastructure that will help revive springs.